Finite element analysis of root canal filling materials in retained primary molars with congenital tooth agenesis - Dogan, Gizem Karagoz; Yavuz, Yelda Polat; Eskibaglar, Busra Karaagac (Peerj Inc, 2025)
Background The selection of an appropriate filling material in root canal treatments of primary molars is crucial for long-term success. However, evaluating the biomechanical behavior of these materials under in vivo conditions remains challenging. This study aimed to investigate the effect of different root canal filling materials on the fracture resistance of the mandibular second primary molar by analyzing stress distributions and failure risk using finite element analysis (FEA) models. Methods A mandibular second primary molar extracted for orthodontic reasons was used in the study. The tooth was scanned using micro-computed tomography (micro-CT) to obtain original DICOM data, which were imported into Geomagic + SpaceClaim 2023R2 to create a solid model. A total force of 330 N was applied to three points on the occlusal surface of each model. The analysis was conducted using Ansys mesh and evaluated with Hyperview 2024. Maximum von Mises (vM) stress values were used to assess stress distribution. Results The highest vM stress in the remaining dentin was observed in the gutta-percha (GP) + AH Plus model (148.5 MPa), followed by mineral trioxide aggregate (MTA) (127.24 MPa), Biodentine (125.65 MPa), and GP + BioRoot RCS (118.37 MPa). Stress concentrations were primarily located in the pericervical region. The GP + AH Plus group showed the highest stress, while the GP + BioRoot RCS group showed the lowest. Among contemporary filling materials, GP + BioRoot RCS demonstrated the lowest dentin stress, suggesting it may offer better root fracture resistance. However, generalizing these findings is difficult due to limited data on primary teeth in the literature. Conclusion The study suggests that GP + BioRoot RCS may be a more promising filling material for enhancing root fracture resistance in primary molars. Further research is needed to validate these findings in clinical settings.
Keywords: Finite element analysis; Primary teeth; Mineral trioxide aggregate; Biodentine